Fahr Disease: Review and case Report - Jha, Prabhat (Nepal Journal of Neuroscience, 2024)
Introduction: Fahr disease is a rare neurodegenerative condition characterized by diffuse calcifications within brain. It is common in the fourth to sixth decade and few cases have been described in pediatric population Case presentation: This case report describes a twelve year old boy with suspected Fahr disease. The clinical presentation was seizure, ataxia, tremor. The patient was managed conservatively with anti seizure medication. Conclusion: Fahr disease is a rare neurodegenerative disease and can present in pediatric population as well. Key words Fahr disease, Pediatric